2007
DOI: 10.1128/jcm.00291-07
|View full text |Cite
|
Sign up to set email alerts
|

Development of Real-Time PCR Assays and Evaluation of Their Potential Use for Rapid Detection of Burkholderia pseudomallei in Clinical Blood Specimens

Abstract: The early initiation of appropriate antimicrobial therapy is critical for improving the prognosis of patients with septicemic melioidosis. Thus, the use of a rapid molecular diagnosis may affect the outcome of this disease, which has a high mortality rate. We report the development of two TaqMan real-time PCR assays (designated 8653 and 9438) that detect the presence of two novel genes unique to Burkolderia pseudomallei. The analytical sensitivity and specificity of the assays were assessed with 91 different B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…A total of 10 false positive soil samples were observed by the two environmental follow-up studies (Kaestli et al, 2007;Trung et al, 2011). These false positives agreed with other qPCR tests (Kaestli et al, 2007;Supaprom et al, 2007), indicating Novak et al's qPCR sensitivity beyond culture for soil samples. Overall, the test approached an environmental accuracy of 100%.…”
Section: B Pseudomalleisupporting
confidence: 67%
See 3 more Smart Citations
“…A total of 10 false positive soil samples were observed by the two environmental follow-up studies (Kaestli et al, 2007;Trung et al, 2011). These false positives agreed with other qPCR tests (Kaestli et al, 2007;Supaprom et al, 2007), indicating Novak et al's qPCR sensitivity beyond culture for soil samples. Overall, the test approached an environmental accuracy of 100%.…”
Section: B Pseudomalleisupporting
confidence: 67%
“…The single false negative soil sample was detected by another method (Supaprom et al, 2007;Trung et al, 2011). Therefore, both Novak et al and Trung et al's procedures could be used on environmental samples (Trung et al, 2011).…”
Section: B Pseudomalleimentioning
confidence: 99%
See 2 more Smart Citations
“…Real-time PCR assays have been developed as rapid identification tools, but several assays were evaluated with strain collections and spiked samples only (30; 40; 41; 43). In fatal septicaemia the amount of bacterial DNA that can be extracted from blood is high enough to be detectable using real-time PCR (38), but a study in Thailand has shown that this diagnostic tool may be of little clinical value when compared with conventional diagnostic approaches (5). MLST analyses have shown that strains from Thailand and Australia can be discriminated and that some sequence types found in environmental samples are underrepresented among clinical isolates thus indicating that they may be less pathogenic for humans (12; 48).…”
Section: Glanders and Melioidosismentioning
confidence: 99%